Karakteristik Uang Elektronik Pada Koin Shopee Berdasarkan Fatwa DSN- MUI No: 146/DSN-MUI/XII/2021 - Bin Lahuri, Setiawan; Rochma Aulia Supandi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2024)
Introduction - This study aims to reveal the statement that Shopee Coin is electronic money comprehensively by using the characteristic approach contained in Shopee Coin with the written regulation of Fatwa DSN-MUI 146/2021 concerning Sharia Electronic Money. Method - To answer this study, primary data collection was used through previous literature and data analysis techniques were carried out using library research, namely by reading, understanding, organizing data, reading repeatedly, making brief notes, identifying categories, interpreting and summarizing data. Result - The results of the study show that the characteristics contained in shopee coins do not have anything in common with the characteristics contained in Electronic Money in the DSN-MUI Fatwa 146/2021, this is divided into several parts, First: in terms of how to get it. Second: the place of storage, the third number, the fourth function, the fifth use, and the sixth lies in the time of use. From these six parts, it can be concluded that Shopee Coin is not electronic money. Implication - In practice, the results of this investigation can be used as a reference by the public, particularly by users of the Shopee marketplace, to refute claims that Shopee coin is electronic money in the form of virtual currency issued by Shopee.